The Message of the Carillon: Bells as Instruments of Colonialism in Twentieth-Century Canada - Nickleson, Patrick (Intersections, 2016)
Bells and carillon have long symbolized the harmonious community in Euro-American political discourse. In this article, I denaturalize this rhetorical position by taking into account the context of bells and carillon in interwar Canada. I do so by reading William Lyon Mackenzie King’s address at the inauguration of the Parliament Hill carillon within the broader context of Canada’s colonial “Old World” nostalgia for the carillon. I then turn to testimony from survivors of the residential school system to argue that the link between bells, harmony, and community had to be forcefully imposed by settlers to banish any potential discord.